Label-Free Detection of Morpholino-DNA Hybridization Using a Silicon Photonics Suspended Slab Micro-Ring Resonator - Soha Yousuf; Jongmin Kim; Ajymurat Orozaliev; Marcus S. Dahlem; Yong-Ak Song; Jaime Viegas (IEEE Photonics Journal, 2021)
In this study, deoxyribonucleic acid (DNA) hybridization was demonstrated using a suspended silicon photonics micro-ring resonator with a 90 nm-thick slab and morpholino as the capture probe. Complementary DNA of various concentrations were tested achieving a surface sensitivity of 2.12 nm/nM, a detection limit of 250 pM, and an intrinsic detection limit of 36.9 pM. A bulk sensitivity of 98 nm/RIU and an intrinsic detection limit of $1.03× 10^{-3}$ RIU was also measured upon exposure to isopropanol/deionized water solutions. With these characteristics, the suspended 90 nm slab ring sensor proved as a promising candidate for lab-on-a-chip bio-sensing applications.